An investigation into the factors that influence toolmark identifications on ammunition discharged from semi-automatic pistols recovered from car fires. Issue 1 (January 2017) - Collender, Mark A.; Doherty, Kevin A.J.; Stanton, Kenneth T.
Abstract: Following a shooting incident where a vehicle is used to convey the culprits to and from the scene, both the getaway car and the firearm are often deliberately burned in an attempt to destroy any forensic evidence which may be subsequently recovered. Here we investigate the factors that influence the ability to make toolmark identifications on ammunition discharged from pistols recovered from such car fires. This work was carried out by conducting a number of controlled furnace tests in conjunction with real car fire tests in which three 9 mm semi-automatic pistols were burned. Comparisons between pre-burn and post burn test fired ammunition discharged from these pistols were then performed to establish if identifications were still possible. The surfaces of the furnace heated samples and car fire samples were examined following heating/burning to establish what factors had influenced their surface morphology. The primary influence on the surfaces of the furnace heated and car fire samples was the formation of oxide layers. The car fire samples were altered to a greater extent than the furnace heated samples. Identifications were still possible between pre- and post-burn discharged cartridge cases, but this was not the case for the discharged bullets. It is suggested that the reason for this is a difference between the types of firearms discharge-generated toolmarks impressed onto the base of cartridge cases compared to those striated along the surfaces of bullets. It was also found that the temperatures recorded in the front foot wells were considerably less than those recorded on top of the rear seats during the car fires. These factors should be assessed by forensic firearms examiners when performing casework involving pistols recovered from car fires. Highlights: Semi-automatic pistols burned in car fire tests. The primary influence on the surface integrity is the formation of oxide layers. Car fire samples are altered to a greater extent than furnace heated samples. Identifications are still possible for discharged cartridge cases after a car fire. Temperatures found to vary significantly within car during fire.